Chemical Composition and Antioxidant and Antimicrobial Activities of Wormwood (Artemisia absinthium L.) Essential Oils and Phenolics - Kamel Msaada; Nidhal Salem; Olfa Bachrouch; Slim Bousselmi; Sonia Tammar; Abdulkhaleg Alfaify; Khaldoun Al Sane; Wided Ben Ammar; Sana Azeiz; Adel Haj Brahim; Majdi Hammami; Sawsen Selmi; et al. (Journal of Chemistry)
The aim of this study was to determine the chemical variability of wormwood extracts as affected by the growing region. Antioxidant and antimicrobial activities were also investigated. The essential oil composition variability of A. absinthium L. aerial parts collected from four different Tunisian regions was assessed by gas chromatography (GC/FID) and by gas chromatography mass spectrometry (GC/MS). In addition, total polyphenols, flavonoids, and condensed tannins as well as antioxidant, antibacterial, and antifungal activities of methanolic extract and essential oils were undertaken. Chromatographic analysis of wormwood essential oils showed the predominance of monoterpene hydrocarbons represented mainly by chamazulene. RP-HPLC analysis of wormwood methanolic extract revealed the predominance of phenolic acids. Antiradical activity was region-dependant and the methanolic extract of Bou Salem region has the strongest activity (CI50=9.38±0.82 µg/mL). Concerning the reducing power, the methanolic extract of Bou Salem, Jérissa, and Boukornine regions was more active than the positive control. Obtained results of antimicrobial activities showed that wormwood essential oil is endowed with important antibacterial activity which was strongly related to the organoleptic quality of oil which appeared strongly region-dependant. A. absinthium L. EOs investigated are quite interesting from a pharmaceutical standpoint because of their biological activities.